The montessori baby ebook A parent's guide to nurturing your baby with love, respect, and understanding. - Davies, Simone (The Parents' Guide to Montessori., 2021)
It’s time to change the way we see babies. Drawing on principles developed by the educator Dr Maria Montessori,  The Montessori Baby  shows how to raise your baby from birth to age one with love, respect, insight, and a surprising sense of calm. Cowritten by Simone Davies, author of the bestselling  The Montessori Toddler , and Junnifa Uzodike, it’s a book filled with hundreds of practical ideas for understanding what is actually happening with your baby, and how you can mindfully assist in their learning and development. Including how to: Prepare yourself for parenthood –physically, emotionally, intellectually, and spiritually. Become an active observer to understand what your baby is really telling you. Create Montessori spaces in your home, including “yes” spaces where nothing is off-limits. Set up activities that encourage baby’s movement and language development at their own pace Raise a secure baby who’s ready to explore the world with confidence.